2021
DOI: 10.3389/fnagi.2021.721428
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics: A Potential Therapeutic Target for Ischemic Stroke

Abstract: Stroke is one of the leading causes of death and disability worldwide. Brain injury after ischemic stroke involves multiple pathophysiological mechanisms, such as oxidative stress, mitochondrial dysfunction, excitotoxicity, calcium overload, neuroinflammation, neuronal apoptosis, and blood-brain barrier (BBB) disruption. All of these factors are associated with dysfunctional energy metabolism after stroke. Mitochondria are organelles that provide adenosine triphosphate (ATP) to the cell through oxidative phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 157 publications
(184 reference statements)
0
38
0
Order By: Relevance
“…Transient permeability can result in mitochondrial swelling, giving rise to rupture of the mitochondrial outer membrane and the release of cytochrome C, which triggers caspase activation. In the present study, overexpression of SH2D5 or treatment with helicid reversed the increased expression levels of Bax, CytC, and cleavage caspase3 and decreased Bcl-2 levels, indicating that SH2D5 or helicid has a strong antiapoptotic effect on central nervous system cell lines [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 81%
“…Transient permeability can result in mitochondrial swelling, giving rise to rupture of the mitochondrial outer membrane and the release of cytochrome C, which triggers caspase activation. In the present study, overexpression of SH2D5 or treatment with helicid reversed the increased expression levels of Bax, CytC, and cleavage caspase3 and decreased Bcl-2 levels, indicating that SH2D5 or helicid has a strong antiapoptotic effect on central nervous system cell lines [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 81%
“…Ischemic stroke results in neural death through complex pathophysiological pathways, including excitotoxicity [70], oxidative stress [71][72][73][74], blood-brain barrier disruption [75], and inflammation [76]. Based on the proposed role for NAAG in preventing excitotoxicity, a neuroprotective effect in stroke seems intuitive.…”
Section: Naag In Strokementioning
confidence: 99%
“…And KEGG analysis revealed that pathways of SAC against IS include Proteoglycans in cancer, Pathways in cancer, Estrogen signaling pathway, Complement and coagulation cascades, Hypertrophic cardiomyopathy (HCM), HIF-1 signaling pathway, Focal adhesion, Arachidonic acid metabolism, PI3K-Akt signaling pathway, etc. It can be seen that these pathways are mainly related to anti-inflammatory, anti-apoptosis, anti-oxidant stress (Duronio, 2008;Huang et al, 2018;Liu et al, 2019) and other physiological and pathological processes, which are also closely related to the pathological process of IS (Zhou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When IS occurs, due to the interruption of blood supply and the destruction of blood brain barrier (BBB), cells in the brain can't maintain normal physiological functions. Then neuron damage and death may occur in the presence of energy depletion, oxidative stress, excitotoxicity, inflammatory response and other pathological factors (Yang et al, 2018;Zhou et al, 2021). The therapeutic effect of existing drugs is not ideal (Ciccone et al, 2013;Saver et al, 2015).…”
Section: Introductionmentioning
confidence: 99%